Preserving Financial Stability - Schinasi, Garry (Economic Issues; Economic Issues ;, 2006)
Spurred by advances in information and computer technologies, financial liberalization and innovation took off inthe late 1970s. Although the changes in financial markets have been beneficial overall, our understanding of the new risks to financial stability lags behind, as demonstrated by the financial crises of the past couple of decades. The study of international financial stability - a public good - is still in its infancy. This pamphlet, aimed at stimulating further debate on the subject, proposes a definition of financial stability and a broad framework for safeguarding it without inhibiting its dynamic development or limiting its benefits.